Ubiquitous fair bandwidth allocation for multimedia traffic on a WiMAX mesh network with multi–channels. (25th May 2012) - Fowler, Scott; Zhang, Xingjun
WiMAX technology can be used as ''last mile ubiquitous'' broadband connections to deliver streaming audio or video to clients. Thus, Quality of Service (QoS) is very important for WiMAX networks. Providing QoS in multi–hop WiMAX networks such as WiMAX mesh networks is challenging since the WiMAX mesh networks MAC is connectionless based. The scheduling function plays a crucial role in QoS support. However, multimedia traffic is bursty in nature, therefore, in this paper, we will discuss the potential unfairness that bursty traffic may be subjected to and propose a new frame–based packet scheduling algorithm.